Specific ion effects on the electrokinetic properties of iron oxide nanoparticles: experiments and simulations. Issue 26 (14th July 2015) - Vereda, Fernando; Martín-Molina, Alberto; Hidalgo-Alvarez, Roque; Quesada-Pérez, Manuel
<x xml:space="preserve">Abstract</x> Specific ion effects have been observed in the magnetite/water interface. Monte Carlo simulations qualitatively explain them in terms of ion size and ionic polarizabilities.